2015
DOI: 10.1080/07908318.2015.1027215
|View full text |Cite
|
Sign up to set email alerts
|

Internationalisation in higher education and its impact in multilingual contexts: redefining identities of Basque-speaking academics

Abstract: This article analyses aspects of the impact of internationalisation in higher education in multilingual contexts where both a state language and a minority language are present and where English is gradually being introduced. The analysis focuses primarily on the consequences for the professional identities of academics who work in a minority language. The basic hypothesis is that the processes of global change influencing higher education go hand in hand with a transformation of the roles of academics and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…They gave two different reasons for these attitudes: the lack of confidence about their proficiency in English and the negative effect that the increasing presence of English can have on Basque. Larrinaga and Amurrio (2015) conducted a study among academic staff and reported that EMI can cause concern and mistrust because of 'the possible reduction and dissolution of the teaching space won for the minority language' (p. 165) but other participants did not see EMI as a threat. The potential effect of English on Basque can also be felt in online discussions.…”
Section: Attitudes Towards Emi Anxiety and Gendermentioning
confidence: 99%
“…They gave two different reasons for these attitudes: the lack of confidence about their proficiency in English and the negative effect that the increasing presence of English can have on Basque. Larrinaga and Amurrio (2015) conducted a study among academic staff and reported that EMI can cause concern and mistrust because of 'the possible reduction and dissolution of the teaching space won for the minority language' (p. 165) but other participants did not see EMI as a threat. The potential effect of English on Basque can also be felt in online discussions.…”
Section: Attitudes Towards Emi Anxiety and Gendermentioning
confidence: 99%
“…These students were in their second year. Even though the university has recently introduced more courses through the medium of English, their number in undergraduate courses is limited and gives rise to different reactions among the teaching staff (Larrinaga & Amurrio, 2015). The rest of the participants (N=135) were young professionals who completed their studies recently and were working in companies and educational institutions of the Basque Country.…”
Section: Participantsmentioning
confidence: 99%
“…In many European and Asian countries (in addition to SK), the internationalization discourse tends to regard English as the only legitimate linguistic tool for instruction and communication in academia (Altbach 2004;Larrinaga and Amurrio 2015;Ljosland 2011). It was thus ironic that Prof. Dave's use of Korean played a critical role in constructing a productive learning community and led to successful outcomes in this FP course.…”
Section: Relativity: Acknowledging the Korean Language As A Fund Of Kmentioning
confidence: 95%
“…Given that globalization means that competition occurs not only locally but also globally (Larrinaga and Amurrio 2015), HEIs have become critical as cultivators of competent individuals who can meet the demands of the competitive global economy (Byun et al 2013;Cheung and Chan 2010). HEI internationalization, which refers to ''any systematic effort aimed at making HE (more) responsive to the requirements and challenges related to the globalization of societies, economy and labour markets'' (Van der Wende 1997, 18, cited in Knight 2008, is thus considered necessary and vital for a country or university to remain competitive worldwide.…”
Section: Higher Education and Sustainable Internationalizationmentioning
confidence: 99%